1972
DOI: 10.1111/j.1469-7998.1972.tb01363.x
|View full text |Cite
|
Sign up to set email alerts
|

Acclimation and energy metabolism of the dingo, Cards dingo and the coyote, Canis latrans

Abstract: Twelve dingos were divided into three groups each containing four animals. One group was warm‐acclimated at +30° to +45°C, the second cool‐acclimated at −20° to − 40°C and a third control group was kept in animal quarters maintained at about +23°C. Three coyotes were also kept in animal quarters but they had free access to outside runs which they used during all seasons. The four warm‐acclimated animals tolerated temperatures of +45°C at 25% relative humidity with a mean rectal temperature of 39.3°C and a mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…Resource selection is dependent on balancing energy expenditures associated with locomotion versus energy intake from prey while minimizing predation risk. Deep snow and cold temperatures, both characteristic of harsh winter climates, can exacerbate locomotion costs for cursorial predators (Shield 1972;Crete and Lariviere 2003) causing a high energetic budget and the need for acquiring substantial food resources. Because of these energetic demands, behavioral and/or morphological adaptations are necessary for a species to effectively travel, hunt, and exploit resources within such deep snow habitats, as demonstrated in Canada lynx (Lynx canadensis) and snowshoe hare (Lepus americanus; Murray and Boutin 1991;Lesage et al 2001;Murray and Larivière 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Resource selection is dependent on balancing energy expenditures associated with locomotion versus energy intake from prey while minimizing predation risk. Deep snow and cold temperatures, both characteristic of harsh winter climates, can exacerbate locomotion costs for cursorial predators (Shield 1972;Crete and Lariviere 2003) causing a high energetic budget and the need for acquiring substantial food resources. Because of these energetic demands, behavioral and/or morphological adaptations are necessary for a species to effectively travel, hunt, and exploit resources within such deep snow habitats, as demonstrated in Canada lynx (Lynx canadensis) and snowshoe hare (Lepus americanus; Murray and Boutin 1991;Lesage et al 2001;Murray and Larivière 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal differences of DEE in free-ranging eutherian mammals have been found in several species, though this is the first time it has been observed in a wild canid. It has been shown that dingoes are capable of acclimating physiologically to extreme temperatures (-41°C to +45°C) over the course of a few months by shifting their TNZ and altering their BMR (Shield 1972). This was observed in concert with a change in thermal conductance brought about by altered coat composition (Shield, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…We calculated DEE using time-energy budgets calculated from our ACC derived behaviours and equations derived from the literature. For resting metabolic rate (applied to all stationary behaviours) we used oxygen consumption data from dingoes collected by Shield (1972) and derived the following equation (Eq 1) for VȮ2 against Ta.…”
Section: Energy Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammals exposed to cold winter conditions cope through two mechanisms; (i) low thermal conductance to minimize heat loss (e.g., thick winter fur and/or insulating fat layer: Shield, 1972;McNab, 1983); or (ii) by reducing their exposure to the cold, through the use of refugia (Noonan et al, 2014(Noonan et al, , 2015, and/or entering a torpid state therein (Harlow, 1981;Lyman, 2013). Thus, while endothermy allows carnivores to exploit cold regions, and higher latitudes (Grigg et al, 2004), fossoriality provides a means of mitigating temperature thresholds (Shelford, 1931;Pörtner, 2002), permitting the species to live in colder FIGURE 3 | Consensus tree of the Feliformia based on phylogenetic relationships from Agnarsson et al (2010).…”
Section: Energetic Adaptationsmentioning
confidence: 99%